PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN MINAT BELI KONSUMEN DI RUMAH MAKAN BOGA-BOGI SURAKARTA - Candra Dewi; Nuryati . (INFORMATIKA, 2014)
Researchers made are search on: "Influence Of Service Quality And Customer Satisfaction Interests Buy Residential Eating Catering-Bogi In Surakarta”. Inthis study a sample of 100 respondents were taken into customers(consumers) Eating Catering-Bogi.The results of path analysis showed that the direct effect of service quality on buying interestis greater than the indirect effect of service quality on buying interest with the mediation of consumer satisfaction. But the total effect to increase buying interest more effectively through customer satisfaction which directly affect the buying interest. Keywords: Quality of Service, Customer Satisfaction, and Interests Buy.